EVALUASI SURVEILANS COVID-19 DI PUSKESMAS BULELENG I KABUPATEN BULELENG - Ni Luh Putu Seri Wardani; I Nyoman Purnawan; Made Nyandra (J-KESMAS: Jurnal Kesehatan Masyarakat, 2021)
This research has the  aim  to  evaluate aspects of  COVID-19  surveillance  input in Buleleng Health Center  I.   The research  design used  is  descriptive  research  with  qualitative approach.  Data  collection techniques used  are  in-depth  interview  techniques  with research informants  as many as  5 people with purposive sampling  techniques  and data retrieval techniques using structured interviews, documentation studies and observations.   The conclusion of  this  study is that man  is not  in accordance  with the  guidelines; methode in accordance  with  the  guidelines  is the availability of  guidelines for  prevention  and prevention of  COVID-19 Disease Rev.5; the allocation of funds has not been in accordance  with the guidelines  because the amount of  funds  available does not match the  increase in  cases  that occur but the source of  funds  is  appropriate; facilities  and  infrastructure   are only  problems of the internet network  that have  not been  in accordance  with  the guidelines